Pemberdayan Masyarakat Pesisir Melalui Edukasi Gizi dan Intervensi Bubur Kacang Hijau untuk Pengendalian Hipertensi di Kelurahan Pantai Amal RT 11 - Nurul Hidayat; Jumadi Jumadi; Suci Wulandari; M. Faldi Kurniawan; Ripka Ingan; Jumaiti Jumaiti; Lola Tersya Fitriani (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This service activity was conducted in RT 11 Pantai Amal Village, East Tarakan District, Tarakan City, North Kalimantan Province on May 6, 2025 at 13.00-17.00 WITA. This activity was conducted at the house of Mrs. Hadirah with the participation of the local community, especially people who have a history of hypertension. This community service activity aims to empower coastal communities in Pantai Amal RT 11 village through nutrition education and intervention of mung bean porridge for hypertension control. The implementation method includes interactive counseling on mung beans, benefits of mung beans, conditions for limiting mung bean consumption, and demonstration on how to prepare modified mung bean porridge, as well as distribution of mung bean porridge to residents with hypertension accompanied by questions and answers related to hypertension. The results of the activity showed an increase in participants' knowledge about the nutritional value of mung bean porridge. This activity also triggered the formation of a community group committed to continuing the program independently. In conclusion, the combination of nutrition education and local ingredient intervention is an effective strategy to empower coastal communities in sustainable hypertension control.